2002
DOI: 10.1088/0264-9381/19/10/312
|View full text |Cite
|
Sign up to set email alerts
|

Chiral splitting and world-sheet gravitinos in higher-derivative string amplitudes

Abstract: We report on progress made in the construction of higher-derivative superinvariants for type-II theories in ten dimensions. The string amplitude calculations required for this analysis exhibit interesting features which have received little attention in the literature so far. We discuss two examples from a forthcoming publication: the construction of the (H NS ) 2 R 3 terms and the fermionic completion of the ǫǫR 4 terms. We show that a correct answer requires very careful treatment of the chiral splitting the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(111 citation statements)
references
References 22 publications
5
106
0
Order By: Relevance
“…In going to quintic, or higher, order of interactions these nonlinear effects can no longer be ignored. This was explicitly verified by the authors of [29], who observed that the linearized superfield cannot reproduce the R 2 H 3 terms in the string-theory effective action.…”
Section: The Linearized Superfieldmentioning
confidence: 70%
“…In going to quintic, or higher, order of interactions these nonlinear effects can no longer be ignored. This was explicitly verified by the authors of [29], who observed that the linearized superfield cannot reproduce the R 2 H 3 terms in the string-theory effective action.…”
Section: The Linearized Superfieldmentioning
confidence: 70%
“…As we have pointed out in [19], these terms sometimes result in additional contributions to the amplitude. In the present situation, however, worldsheet gravitino terms are harmless.…”
Section: Introductionmentioning
confidence: 87%
“…As argued in 3 Representations of the Lorentz group Spin(1,10) are specified with standard Dynkin labels, where (10000) is the vector and (00001) the spinor. Note that only the representations relevant for the conventional constraints are explicitly displayed.…”
Section: Implementation Of the Conventional Constraintsmentioning
confidence: 99%